ON F-z-SUPPLEMENTED SUBGROUPS OF FINITE GROUPS - 郭文彬 唐娜 李保军 (Acta mathematica scientia, 2011)
A subgroup H of a group G is called F-z-supplemented in G if there exists a subgroup K of G, such that G = HK and H∩K≤ Z∞F（G）, where Z∞F（G） is the F-hypercenter of G. We obtain some results about the F-z-supplemented subgroups and use them to determine the structure of some groups.